Antidepressant Prescription to Children/Adolescents and Its Effects on the Cardiovascular System, Comprising the Actual Questions of Periodicity of the Checkups, Cooperation among Pediatricians, Family Doctors, Cardiologists and Children-Adolescent Psychiatrists - Montvilaitė, Reda (Acta medica Lituanica, 2025)
Background: Pharmacological treatment is one of the most effective ways to help psychiatric patients with depressive disorders. However, prescription of antidepressants to children and adolescents creates controversial thoughts due to possible negative effects on the cardiovascular system. Despite being beneficial in controlling serious illnesses, there is less research done on the side effects of antidepressants which would require periodical checkups and cooperation among medical specialists. This literature review was completed to evaluate effects of antidepressants on the cardiovascular system and the necessity of regular assessment while treating children and adolescents.Aim: To review the cardiovascular effects of antidepressants prescribed to children and adolescents; to discuss the need for regular patient checkups with a multidisciplinary team: pediatricians, family doctors, cardiologists and children-adolescent psychiatrists.Methodology: Literature sources were selected from the Pubmed, Google Scholar, Clinical Key, and Research Gate databases by following dates from 2013 to 2024 while using the following keywords and their combinations: antidepressant, cardiovascular, side effects, cardiovascular risk, children and adolescents, selective serotonin reuptake inhibitors (SSRIs), serotonin-norepinephrine reuptake inhibitors (SNRIs), tricyclic antidepressants (TCAs), psychotropic medication, antidepressants in pediatrics, atypical antidepressants, benzodiazepines, lipid metabolism.Results: Antidepressants, including SSRIs, SNRIs, TCAs, atypical antidepressants and benzodiazepines, are associated with significant cardiovascular risks in children and adolescents. SSRIs, like citalopram and escitalopram, can disturb the heart rhythm by prolonging the QT interval, or increasing the risk of serious arrhythmias. SNRIs have been linked to an elevated blood pressure and heart rate. TCAs are known for their proarrhythmic effects, particularly in overdose situations, posing a high risk of sudden cardiac events. Atypical antidepressants like bupropion can cause cardiovascular disturbances, especially when overdosed. Additionally, less commonly prescribed benzodiazepines contribute to cardiovascular risks when combined with SSRIs during pregnancy, due to increasing the likelihood of congenital heart defects. These risks underscore the importance of careful monitoring, dosage management and thorough cardiovascular assessment when prescribing these medications to children, adolescents, and pregnant women. A team consisting of professional specialists – children-adolescent psychiatrists, cardiologists, pediatricians and family doctors – should detect long-term effects of pharmacotherapy by checking up the young patients regularly.Conclusions: The use of antidepressants in children and adolescents, though crucial for managing severe psychiatric disorders, raises significant cardiovascular safety concerns. SSRIs, SNRIs, TCAs, atypical antidepressants, and benzodiazepines have varying cardiovascular risks, especially in vulnerable youth populations and during the prenatal period. Given these risks, careful prescribing, close monitoring, creating guidelines and collaboration among healthcare providers are essential to ensure safe and effective treatment. Additionally, more research is needed to fully understand the long-term cardiovascular impacts of these medications in the pediatric population.